Pengelolaan Sistem Informasi Karya Ilmiah - Ulum, Amirul (Pustakaloka, 2011)
Today, many libraries such as academic library havedeveloped local digital repositories. A significant increase inthe development of repositories is expected with technology andprocess improvements for digital collection development. Currentinformation technology requires interoperability between systemsthat facilitate the exchange of data and information. Use of the webbased applications and systems that have the ability to exchangeinformation and data through Open Archives Initiative (OAI)protocol or the other systems can be a bridge to access the localdigital collection. This study discusses about the implementationof information system using free software Eprints. The result isan Eprints can be used as an information system for institutionalrepositories that has interoperability with other system